(untitled) (Archive of Conferences, 2021)
The article analyzes the wild relatives of cultivated plants from the Fabaceae Lindl. Family, the flora of Aralkum by their life forms. Analysis of the synopsis showed that the DSCR meeting on the Aralkum consists of 4 genera and 5 species, and the presence of at least 4 different life forms was revealed. Of these, 2 semi-shrubs, 2 perennial grasses and 1 annual grass